Cape gooseberry is remunerative fruit - Bakshi, Parshant; Bhushan, Bharat; Jasrotia, Amit (Indian Horticulture, 2015)
Diversification in horticulture is the need of the day, particularly for farmers having small land holding like Jammu province. Cape gooseberry can be a very good option as this crop has low lag period, ripen within few months of planting and can be used as an intercrop. Thus, it becomes imperative to introduce this fruit in different parts of the country where agroclimatic conditions are suitable for its cultivation.